1975
DOI: 10.1111/1523-1747.ep12607659
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Spermidine And Spermine Levels In The Blood Of Psoriasis Patients

Abstract: Samples of blood, anticoagulated with EDTA, from 11 patients with psoriasis and 11 individuals without psoriasis were analyzed for their polyamine content. The average spermidine level in patients with psoriasis was approximately twice that of the controls and the average spermine level was three times that of the controls. The level of spermidine and spermine in the skin of two patients with psoriasis were significantly depressed as compared to those of controls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 12 publications
1
19
0
Order By: Relevance
“…[11] Polyamine levels in blood, urine, and other biological fluid fluctuated in accordance with psoriasis activity. [12] SPD/SM ratio, considered as an indicator of proliferation activity, was found increased in psoriatic lesions, compared to non-lesional skin of patients affected by the disease. [13] Interestingly, patients with psoriasis receiving etretinate showed significant drop of all urinary polyamines, with the greatest prevalence of SM.…”
Section: Discussionmentioning
confidence: 99%
“…[11] Polyamine levels in blood, urine, and other biological fluid fluctuated in accordance with psoriasis activity. [12] SPD/SM ratio, considered as an indicator of proliferation activity, was found increased in psoriatic lesions, compared to non-lesional skin of patients affected by the disease. [13] Interestingly, patients with psoriasis receiving etretinate showed significant drop of all urinary polyamines, with the greatest prevalence of SM.…”
Section: Discussionmentioning
confidence: 99%
“…Callus extracts were minimally stimulated. Since spermidine and spermine levels have been reported to be elevated in psoriatic plaques (Proctor et al, 1975), it is possible that the higher ribonuclease levels observed in psoriatic extracts may reflect higher endogenous polyamine levels. If the psoriatic ribonucleases are already optimally stimulated, further addition of polyamines may raise the polyamine concentration to a value which depresses activity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The concentration of spermine in the whole blood of psoriatic patients is increased twoto threefold above normal, and there is also an elevation of spermidine (PROCTOR et al 1975;COOPER et al 1978). More detailed investigation (COOPER et al 1978) reveals increased amounts associated with the erythrocytes but not with the leucocytes.…”
Section: Polyamine Metabolismmentioning
confidence: 92%
“…Early findings using only a few subjects actually suggested a reduction of skin polyamines in psoriasis (STiiTTGEN 1968;PROCTOR et al 1975), but all other studies have shown a statistically significant increase in putrescine, spermidine and spermine over normal controls in involved psoriatic epidermis (RUSSELL et al 1978 b;BOHLEN et al 1978;GROSSHANS et al 1978;PROCTOR et al 1979;LAUHARANTA et al 1981). Early findings using only a few subjects actually suggested a reduction of skin polyamines in psoriasis (STiiTTGEN 1968;PROCTOR et al 1975), but all other studies have shown a statistically significant increase in putrescine, spermidine and spermine over normal controls in involved psoriatic epidermis (RUSSELL et al 1978 b;BOHLEN et al 1978;GROSSHANS et al 1978;PROCTOR et al 1979;LAUHARANTA et al 1981).…”
Section: Polyamine Metabolismmentioning
confidence: 99%